Glussa GYM : business plan : lightweight baby! - Jón Ingi Þrastarson 1987- (2011)
The purpose of this business plan was to evaluate the potential demand for running a Fitness- and CrossFit Center in Akranes. Another aim was to find out if set Fitness- and CrossFit Center would generate profits from its operations. It was the authors believe that there could be a market opportunities in Akranes because of its increase in population and possible saturation at present centers. In making of this business plan the framework which is defined in the book Principles of marketing by Philip Kotler, Gary Armstrong, Veronica Wong and John Saunders was utilized. SWOT and Porter‟s Five Force analysis among other were used to estimate the internal and environmental position on the market. The marketing environment was examined and possible strategies to attain market share were evaluated, through various advertisement channels. Secondary data was mostly used in research The estimated start up costing is 48 million ISK which will be funded through investors and loan. The startup costing will cover renovations of the housing as well as importing all the equipment needed. With the set premises in sales and cost Glussa GYM is estimated to generate losses all throughout the five year plan which the business plan expands. It is the author‟s conclusion that with given premises there is no base for a Fitness- and CrossFit Center in Akranes. Further recommendations would be for the founders to evaluate to operate only a CrossFit Center in Akranes which is much more cost efficient.